Long Non-coding RNA FEZF1-AS1 Promotes Growth and Reduces Apoptosis Through Regulation of miR-363-3p/PAX6 Axis in Retinoblastoma - Liu, Xiuming (Biochem Genet, 2021)
Retinoblastoma is the most common malignancy in children's eyes with high incidence. Long non-coding RNAs (lncRNAs) play important roles in the progression of retinoblastoma. LncRNA FEZF1 antisense RNA 1 (FEZF1-AS1) has been found to stimulate retinoblastoma. However, the mechanism of FEZF1-AS1 underlying progression of retinoblastoma is still unclear. In current study, FEZF1-AS1 was up-regulated in retinoblastoma tissues and cells. FEZF1-AS1 overexpression enhanced retinoblastoma cell viability, promoted cell cycle, and inhibited apoptosis. Conversely, FEZF1-AS1 knockdown reduced cell viability, cycle, and elevated apoptosis. The interaction between FEZF1-AS1 and microRNA-363-3p (miR-363-3p) was confirmed. FEZF1-AS1 down-regulated miR-363-3p and up-regulated PAX6. PAX6 was a target gene of miR-363-3p. EZF1-AS1 promoted retinoblastoma cell viability and suppressed apoptosis via PAX6. Further, we demonstrated that FEZF1-AS1 contribute to tumor formation in vivo. In conclusion, FEZF1-AS1 elevated growth and inhibited apoptosis by regulating miR-363-3p/PAX6 in retinoblastoma, which provide a new target for retinoblastoma treatment.